Networking Universities and Hospitals: A Case Study of Research and Commercialization in the Taiwanese Herbal Medicine Sector. Issue 4 (2nd October 2021) - Fung, Hon-Ngen; Tan, Consilz
Abstract: This paper provides an empirical account of the case of Taiwan in her innovative efforts in the herbal medicine sector through scientific and technological development. This study aims to propose a network analysis approach, which is typically found in innovation studies, to illustrate the sociological dimensions of actor network theory. The sector is of interest from a social studies of science perspective due to the collision between traditional knowledge philosophies, which are well accepted in East Asian communities, and scientific regulatory standards, that have raised issues regarding the legitimacy and safety of the products. This study considers the actor network linkages between universities, government and industry which act as indicators of knowledge diffusion and collaboration. Relevant records were captured using a heuristic search string and was used to visualize: (i) the number of researchers (agglomeration denoted by the size of bubbles), (ii) organizational linkages through co-authorship (connectedness indicated by the presence of lines between organizations), and (iii) position of the organization (centrality in relation to other organizations). The case presented in this study takes a snapshot of how an advanced economy such as Taiwan, has developed a productive innovation system for herbal medicine. The development of the actor network has evolved mainly from productive working relationships in a close-knit community of researchers that mainly interact through the research organizations in Taipei.